2013 Proceedings of the ESSCIRC (ESSCIRC) 2013
DOI: 10.1109/esscirc.2013.6649099
|View full text |Cite
|
Sign up to set email alerts
|

A 0.18-&#x00B5;m CMOS, &#x2212;92-dB THD, 105-dB<inf>A</inf> DR, third-order audio class-D amplifier

Abstract: This paper presents a third-order audio class-D amplifier, implemented in a 0.18-μm CMOS technology, achieving −92 dB of total harmonic distortion (THD) and 105 dBA of dynamic range (DR) with a quiescent current of 2 mA. The circuit delivers up to 2.4 W on a 4-Ω load with a peak efficiency of 88%. The THD performance, achieved thanks to the thirdorder loop filter, makes the proposed device suitable for high-end audio applications, where linear amplifiers are still the dominant solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It remains unclear why the f sw regulated case has higher distortion than the fixed frequency cases. For applications that require lower distortion, a higher-order feedback loop can be used, either for hysteretic feedback [25] or fixed carrier [26], [27] topologies.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…It remains unclear why the f sw regulated case has higher distortion than the fixed frequency cases. For applications that require lower distortion, a higher-order feedback loop can be used, either for hysteretic feedback [25] or fixed carrier [26], [27] topologies.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…A varying common-mode level of Vtune level might be one of the contributing factors. For applications that require lower distortion, a higher-order feedback loop can be used, either for hysteretic feedback [49] or fixed carrier [50], [51] topologies.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…Class-D power stage non-idealities introduce distortion to the amplifier's output signal [47], [48]. Feedback loop gain can suppress these error and various high-order feedback loops with sufficient loop gain are implemented for this reason [49]- [51]. Yet it has been shown that higher-order loop filters does not necessarily mean better linearity performance due to the extra error introduced by the PWM-based feedback loop itself [52]- [54].…”
Section: Linearitymentioning
confidence: 99%
See 1 more Smart Citation